Regulating the Performance of Lithium-Ion Battery Focus on the Electrode-Electrolyte Interface - Zhao, Dongni; Li, Shiyou (Frontiers in Chemistry, 2020)
The development of lithium ion battery has gone through nearly 40 years’ research. The solid electrolyte interface film for LIB is one of most vital research topic. Its performance affects the cycle life and safety of LIBs to a large degree. Progress in understanding the SEI layers on Li-ion negative and positive electrodes has obtained considerable research in the past few decades, but much remains to be understood at the fundamental level and there is still much controversy in the composition and film-forming mechanism of interfacial film. In this paper, we summarize the research on the interface film in recent years, including the film formation mechanism, composition and stability of the interface film on the positive electrodes (including in the dilute and high concentration electrolytes). The induction of the test method and advanced characterizations are also introduced. Finally, the future development of the interface film and the urgent problem need to be solved are put forward to.